Answer:
[tex]f(n) = f(n- 1) * 2[/tex]; [tex]f(1) = 3[/tex]
Step-by-step explanation:
Given
[tex]1\ minute = 3\ friends[/tex]
Every other minute
[tex]Each\ friend = 2\ other\ friends[/tex]
Required
Determine the recursive function
Let the number of minutes be represented with n.
The initial condition can be represented as:
[tex]n = 1[/tex]
[tex]f(1) = 3[/tex] --- i.e. 3 friends initially at the first minute
At every other minutes:
[tex]n \ge 2[/tex] i.e 2 minutes upwards
This means that n follows the following sequence
[tex]n \to n, n -1, n -2,n -3, n - 4,.....,4,3,2[/tex]
Note that the difference between each term is 1.
This means that recursive function has to be defined backwards i.e.
[tex]f(n) = f(n- 1) * k[/tex]
Where k = 2
i.e. The number of friends that received the video from each friend
So, we have:
[tex]f(n) = f(n- 1) * 2[/tex]
Hence, the recursive function is:
[tex]f(n) = f(n- 1) * 2[/tex]; [tex]f(1) = 3[/tex]